CURRENT PROBLEMS IN MEDICAL SOCIOLOGY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The authors of this article attempt to analyze the existing models of medical ethics and some of the issues associated with them today. The article presents the authors’ views on various aspects of medical ethics in society, emphasizing its significance, and analyzes the unique features of the models within the field of medical ethics.